Individuality and feminine production through Lolita urban fashion - Rochedo, Aline Lopes (Revista de Antropologia, 2021)
This article is the result of an ethnographic exercise accomplished with Brazilian followers of Lolita urban fashion, a Japanese style created in the 1970s and inspired by Victorian doll clothing combined with rococo elements and Japanese pop culture. The aesthetics spread throughout the world from the 1990s. I explore the experience of dressing Lolita and, through it, the perception of self and the production of individualities associated with the performance of gender. I try to demonstrate how this specific outfit reiterates the excess as a sign of the feminine, even when used on men’s bodies.